Preeclampsia knowledge among women in Utah - Jessica Wilkinson; Gene Cole (Taylor & Francis Group, 2018)
Background: Despite the benefits of preeclampsia (PE) education in improving health outcomes, little is known about how often healthcare providers in Utah include PE in prenatal education or how much information women retain. As such, the purpose of this study was to explore PE awareness among mothers in Utah and inquire how often PE is included in prenatal education. Factors associated with PE knowledge were also investigated. Methods: A cross-sectional survey was conducted. Questions were created from two Preeclampsia Awareness Surveys developed by the Preeclampsia Foundation. PE knowledge was measured with 29 items from the 2014 Preeclampsia Awareness Survey, and a knowledge score was calculated. Results: A total of 340 women completed the survey. Over half (56.7%) of women reported their healthcare provider described the signs and symptoms of PE to them. The mean PE knowledge score was 17.07. Hearing of PE from a healthcare provider, having the signs and symptoms of PE described by a healthcare provider and having a history of PE were significantly associated with a higher PE knowledge score. Conclusions: Patient awareness is essential to the successful management of PE. The need for improved PE education in Utah was evident in this survey. As not all healthcare providers are diligent in instructing patients regarding PE, more research is needed to fully assess the knowledge of mothers and examine the practices of providers. An explanation of PE signs and symptoms should be given to all women at prenatal care visits to improve health outcomes.